La ingeniería de sistemas en el cambio hacia un enfoque por procesos empresariales y soluciones ERP - Vasquez Torres, Augusto Vladimir (2022)
Taking into account that the professional career developed in 15 years was dedicated to the implementation of SAP Solutions (Systemanalyse und Programmentwicklung), Systems Analysis and Program Development; German company dedicated to the development of software for business process management. The purpose of this report is to explain the professional performance from the technical, management and continuous learning perspective, developed in the different national and international brand companies where I was highlighted. Part of my job is the information gathering of business processes from different industries, understanding them together with the business and leading to improvement, simplification and automation; hand in hand with SAP technology solutions. During professional development, important achievements and recognitions have been generated, developing technical capacities, and the ability to manage projects under project management methodologies, mainly the ASAP methodology (Accelerated SAP ASAP) and SAP Activate, capacity for continuous learning, exploring and generating self-learning in technological solutions and trends worldwide, and also demonstrating that during all this time I have developed a high professional level, respecting and applying the values and standards that the engineering professional must develop in the field of their functions.